2016
DOI: 10.1016/j.drugpo.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extended public transport operating hours and venue lockout policies on drinking-related harms in Melbourne, Australia: Results from SimDrink, an agent-based simulation model

Abstract: A two-hour extension of PT is likely to be more effective in reducing verbal aggression and consumption-related harms than venue lockouts. Modelling a further extension of PT to 24h had minimal additional benefits but the potential to displace incidents of verbal aggression among OU residents from private to public venues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…A more direct method of addressing street‐based incidents of aggression may be by extending public transport operating hours, which is being trialled in Melbourne in the form of 24‐hour public transport on Friday and Saturday nights. Not only has similar modelling work shown that this policy may be more effective in reducing incidents of aggression than venue lockouts, 19 but it is likely to have more public support and subsequently face fewer political barriers. It remains to be seen how the introduction of 24‐hour public transport in Melbourne has actually affected individual behaviours and drinking‐related harms, in particular those of OU residents who have increased access to IC entertainment precincts late at night; for example it is plausible that these individuals may start their nights out later or have different movement patterns between venue types as a result of the policy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A more direct method of addressing street‐based incidents of aggression may be by extending public transport operating hours, which is being trialled in Melbourne in the form of 24‐hour public transport on Friday and Saturday nights. Not only has similar modelling work shown that this policy may be more effective in reducing incidents of aggression than venue lockouts, 19 but it is likely to have more public support and subsequently face fewer political barriers. It remains to be seen how the introduction of 24‐hour public transport in Melbourne has actually affected individual behaviours and drinking‐related harms, in particular those of OU residents who have increased access to IC entertainment precincts late at night; for example it is plausible that these individuals may start their nights out later or have different movement patterns between venue types as a result of the policy.…”
Section: Discussionmentioning
confidence: 99%
“…For this analysis, the model outputs used to compare different scenarios were: the number of incidents of verbal aggression inside public and private venues; the number of incidents of verbal aggression outside of public venues (‘street‐based’ incidents); and the percentage of agents from the OU and IC areas experiencing consumption‐related harms. The effect of venue lockout policies on transport‐related harms experienced by agents in the model have been considered elsewhere 19 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations